Phenotypic and transcriptional characterization of F. tularensis LVS during transition into a viable but non-culturable state - Cantlay, Stuart; Garrison, Nicole L.; Patterson, Rachelle; Wagner, Kassey; Kirk, Zoei; Fan, Jun; Primerano, Donald A.; Sullivan, Mara L. G.; Franks, Jonathan M.; Stolz, Donna B.; Horzempa, Joseph (Frontiers in Microbiology, 2024)
Francisella tularensis is a gram-negative, intracellular pathogen which can cause serious, potentially fatal, illness in humans. Species of F. tularensis are found across the Northern Hemisphere and can infect a broad range of host species, including humans. Factors affecting the persistence of F. tularensis in the environment and its epidemiology are not well understood, however the ability of F. tularensis to enter a Viable But Non-Culturable state (VBNC) may be important. A broad range of bacteria, including many pathogens, have been observed to enter the VBNC state in response to stressful environmental conditions, such as nutrient limitation, osmotic or oxidative stress or low temperature. To investigate the transition into the VBNC state for F. tularensis, we analyzed the attenuated live vaccine strain, F. tularensis LVS grown under standard laboratory conditions. We found that F. tularensis LVS rapidly and spontaneously enters a VBNC state in broth culture at 37°C and that this transition coincides with morphological differentiation of the cells. The VBNC bacteria retained an ability to interact with both murine macrophages and human erythrocytes in in vitro assays and were insensitive to treatment with gentamicin. Finally, we present the first transcriptomic analysis of VBNC F. tularensis, which revealed clear differences in gene expression, and we identify sets of differentially regulated genes which are specific to the VBNC state. Identification of these VBNC specific genes will pave the way for future research aimed at dissecting the molecular mechanisms driving entry into the VBNC state.